Evaluating the Effectiveness of Problem-Focused Coping Strategies in Reducing Vocational High School Students’ Anxiety About Entering the Workforce - Isrizal Anwar Zuhri; Carolina Ligya Radjah; Lutfi Fauzan (Pro Panoramic Solution, 2025)
This study aims to examine the effectiveness of group counseling based on Cognitive Behavioral Therapy (CBT) using problem-focused coping strategies in reducing vocational high school students’ anxiety when preparing to enter the workforce. The study employed an experimental research method with a one-group pretest–posttest design. The sample consisted of six vocational high school students identified as having high levels of anxiety. Data were collected using two anxiety scale instruments: the first for screening purposes and the second for pretest and posttest measurements. The data were analyzed using the nonparametric Wilcoxon signed-rank test. The results indicated a significant difference between pretest and posttest scores (Z = -2.201, p = 0.028; p < 0.05). Therefore, the null hypothesis was rejected. It can be concluded that group counseling based on Cognitive Behavioral Therapy using problem-focused coping strategies is effective in reducing students’ anxiety in preparing to enter the workforce.